2021
DOI: 10.1093/ofid/ofab232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inadequate Empiric Antibacterial Therapy on Hospital Outcomes in SARS-CoV-2-Positive and -Negative US Patients With a Positive Bacterial Culture: A Multicenter Evaluation From March to November 2020

Abstract: Background Increased utilization of antimicrobial therapy has been observed during the coronavirus disease 2019 pandemic. We evaluated hospital outcomes based on the adequacy of antibacterial therapy for bacterial pathogens in US patients. Methods This multicenter retrospective study included patients with ≥24 hours of inpatient admission, ≥24 hours of antibiotic therapy, and discharge/death from March-November 2020 at 201 US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…It’s vital to emphasize that these outcomes are primarily influenced by bacterial infections rather than viral ones. 244 …”
Section: Pneumonia and Covid-19mentioning
confidence: 99%
“…It’s vital to emphasize that these outcomes are primarily influenced by bacterial infections rather than viral ones. 244 …”
Section: Pneumonia and Covid-19mentioning
confidence: 99%
“…Concurrent bacterial and fungal infections have played an important role in hospital outcomes during the COVID-19 pandemic [7]. Recently, Bassetti et al [8 ▪▪ ], provided a global overview of the prevalence of Staphylococcus aureus and methicillin-resistant S. aureus in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent bacterial and fungal infections have played an important role in hospital outcomes during the COVID-19 pandemic [ 9 ]. Recently, Bassetti et al provided a global overview of the prevalence of S. aureus and methicillin-resistant S. aureus (MRSA) in this population and confirmed that MRSA was a common causative agent of pneumonia in patients with COVID-19 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%